Effects of Foreign Direct Investment in Sub-Saharan Africa Economic Growth: Evidence from Panel Data Analysis - Dike, Christie (International Journal of Economics and Financial Issues, 2018)
Agriculture is the strength of the most Sub-Saharan Africa (SSA) Countries; it promotes significantly to the production of food and raw materials for businesses, and expands opportunities for foreign exchange earnings. Foreign Agricultural Investment is an important source of capital inflow that stimulates economic growth. This paper examines the presence of a long-run positive relationship between Foreign Agricultural Investment and economic growth in the SSA region by using the dynamic panel VECM technique. We justify that there is a positive link between Foreign Agricultural Investment and economic growth in the long run. Keywords: Foreign Direct Investment, Economic Growth, Panel VECM, Sub Saharan Africa (SSA) Countries. JEL Classifications: F21, O40, O55